Molecular analysis of atypical deep penetrating nevus progressing to melanoma. (6th July 2020) - Isales, Maria C.; Khan, Ayesha U.; Zhang, Bin; Compres, Elsy V.; Kim, Daniel; Tan, Timothy L.; Beaubier, Nike; Gerami, Pedram
Abstract: Deep penetrating nevi (DPN) are dermal‐based, heavily pigmented melanocytic proliferations primarily resulting from mutations in B‐catenin and BRAF or, less commonly, NRAS . DPNs are considered to be intermediate grade tumors which are stable with low risk of malignant transformation. The precise risk for transformation is unknown. Only rare cases of DPN progressing to melanoma have been described. We present a case of a 53‐year‐old female with a blue‐black thigh lesion, on histopathology illustrating a melanocytic proliferation with morphology most consistent with a DPN progressing to melanoma. Targeted next generation sequencing performed on both the atypical melanocytic proliferation and melanoma components showed NRAS and CTNNB1 mutations but no evidence of TERT promoter mutation or chromosomal copy number aberrations. The melanoma had additional mutations including a hotspot TERT promoter mutation as well as unbalanced chromosomal copy number aberrations. This report details the progression of DPN to melanoma through a prominent ultraviolet signature and acquisition of genetic aberrations. While the vast majority of DPNs are benign stable nevi, there are rare examples, which may progress to melanoma. This report documents a case and shows the molecular evolution by which the tumor transformed to melanoma.